The tracks of the megaterium. Anatomical comparision between Eremotherium Rusconii and Bradypus Variegatus - Ricaurte Viveros; Catalina Lara; Manuel Hoyos; Mario Murcia (Acta Biológica Colombiana, 2004)
Based on an anatomical comparison between Eremotherium rusconii and Bradypus variegatus and a literature review, similarities and differences between these species were established in an attempt to explain the extinction of E. rusconii. Proportions between femur and humerus, scall, hair, nails and metabolism were compared. Based on this, it appears that B. variegatus survival was related to its smaller size and feeding habits.